American Revolution : biographies - Schmittroth, Linda; Rosteck, Mary Kay; McConnell, Stacy A. (Detroit : U. X. L., 2000)
Profiles sixty men and women who were key players on the British or American side of the American Revolution, from John Adams, who became the second president, to Eliza Wilkinson, who wrote of the day British soldiers looted her South Carolina home
v. 1. A - J -- v. 2. K - Z.
Includes bibliographical references and index
Keywords: United States -- History -- Revolution, 1775-1783 -- Biography -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Biography